ANALISIS PENERIMAAN APLIKASI E-LEARNING MENGGUNAKAN TECHNOLOGY ACCEPTANCE MODEL (TAM) - Luluk Suryani; ery murniyasih (LPPM Poltek ST Paul, 2021)
The current pandemic has had a huge impact in many things in the world of education. Before the pandemic, Saint Paul Polytechnic, Sorong had a website-based e-learning application that was used for helping all students in studying. During the pandemic, lecturers and students further have been maximizing the use of e-learning as the lecturing is held via online. Since the e-learning application was implemented at the Saint Paul Sorong Polytechnic, an analysis of the level of user acceptance of e-learning applications has never been carried out. In this study, an analysis of the level of student acceptance of the e-learning application will be carried out. The number of respondents involved is 50 students that are from the Computer and Network Engineering Department. The analysis will be carried out using the Technology Acceptance Model (TAM). The application acceptance test will be carried out by looking at the relationship between each variable in the TAM model which consists of Perceived Usefulness (PU), Perceived Ease of Use (PEU), Behavioral Intention (BI), Attitude Toward Using (ATU), and Actual Usage (AU). ). The statistical tests performed were the validity test, reliability test and F test on the linear regression statistical formula. After the research process was carried out, it is found that several variables had a significant effect on other variables. PEU variable has a positive effect on PU with a value of 187.095. PU variable has a positive effect on ATU with a value of 92.895. PEU has a positive effect on ATU with a value of 103.443. ATU has a positive effect on BI with a value of 17.522. PU has a positive effect on BI with a value of 40.340. BI has a positive effect on AU with a value of 53.319.